Electron deficient nanoclusters of platinum and palladium on porous silicon - N. A. Yashtulov (Тонкие химические технологии)
The platinum and palladium nanoparticles on the porous silicon were synthesized by radiation - chemical reduction in the solution of reversed micelles. The Pt and Pd nanoclusters obtained are electron deficient.